2015
DOI: 10.1007/s10620-015-3624-x
|View full text |Cite|
|
Sign up to set email alerts
|

Worldwide Burden of Gastric Cancer Attributable to Tobacco Smoking in 2012 and Predictions for 2020

Abstract: Smoking accounts for a larger number of gastric cancer cases among men, and gender differences are expected to increase in the next decade, despite the decrease in PAFs. Intensified efforts to control smoking are needed to further reduce the burden of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
2
23
1
1
Order By: Relevance
“…Our OR estimates for current cigarette smokers were, if anything, slightly lower than those on the basis of published studies, which found risks ranging between 1.5 and 1.7 (Tredaniel et al, 1997; Ladeiras-Lopes et al, 2008; La Torre et al, 2009;Bonequi et al, 2013), resulting in an estimated worldwide population attributable fraction of 19.5% in men and 3.0% in women (Peleteiro et al, 2015). Publication bias may have led to an overestimation of the risk in the published literature.…”
Section: Discussioncontrasting
confidence: 82%
“…Our OR estimates for current cigarette smokers were, if anything, slightly lower than those on the basis of published studies, which found risks ranging between 1.5 and 1.7 (Tredaniel et al, 1997; Ladeiras-Lopes et al, 2008; La Torre et al, 2009;Bonequi et al, 2013), resulting in an estimated worldwide population attributable fraction of 19.5% in men and 3.0% in women (Peleteiro et al, 2015). Publication bias may have led to an overestimation of the risk in the published literature.…”
Section: Discussioncontrasting
confidence: 82%
“…It was previously reported that smokers had higher levels of DOUX2 expression in the tracheal and airway epithelium than nonsmokers [ 34 ]. Smoking is a contributing factor of the carcinogenesis of gastric cancer [ 31 , 35 ]. Recently it has been reported that smoking suppresses regulatory B cell and inhibits the production of interleukin 10; both events may increase the risk of gastric cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori is now well known to be linked to stomach cancer in many studies along with EBV [14–18]. Other risk factors for GC include chronic gastritis [9], older age [19], male sex [20, 21], a diet high in salt [22–24], smoking [25, 26], alcohol consumption [27], poorly preserved foods [28], diet low in fruits and vegetables [29], tobacco product [30], pernicious anaemia [3133], a history of stomach surgery for benign conditions [34], and a family history of stomach cancer [34, 35]. …”
Section: Introductionmentioning
confidence: 99%